Konsep Dasar Pendidikan Islam Inklusif : Studi Tentang Inklusivitas Islam Sebagai Pijakan Pengembangan Pendidikan Islam Inklusif - Purnomo, Purnomo; Solikhah, Putri Irma (J-PAI: Jurnal Pendidikan Agama Islam, 2021)
The paradigm shift in the inclusive Islamic education curriculum is an essential part of Presidential Decree No. 7 of 2021. There is a tendency for religious learning to be normative-indoctrinative and lead to truth claims, raising suspicions that religious education contributes to the generation of extreme views. PPIM UIN Jakarta research shows that the PAI curriculum is still ambiguous on the issue of tolerance, and there is a tendency for PAI teachers to have an intolerance opinion towards minorities by 34%, and towards adherents of other religions by 29%. This study discusses the concept of inclusive education in Islam, the urgency of inclusive Islamic education, and the paradigm shift from exclusive to inclusive. This research is a literature study with a rationalistic approach. Data analysis uses reflective thinking logically to interpret the inclusive values of Islamic education and reflect them into strategic steps to answer the challenge of exclusivity. This study shows that Islam carries an inclusive spirit characterized by terminologies such as at-ta'arruf, at-tasammuh, at-tawassuth, and at-ta'awun. The urgency of inclusive Islamic education is intended so that the character of inclusive Islam is truly taught in learning. To change the paradigm of Islamic education from exclusive to inclusive, improvements are needed in curriculum elements, educators, and learning strategies.